Cell wall remodeling–dependent morphotype switch in Mycobacterium avium differentially regulates colonization and tissue persistence - Katie Laschanzky; Giulia Magri Ribeiro; Rodrigo Sequeira; Sacha Cancade; Fredric Carlsson; Julia Lienard (Proceedings of the National Academy of Sciences, 2026)
Species of the Mycobacterium avium complex display two main colony morphologies, smooth transparent (SmT) and smooth opaque (SmO), where SmT is associated with human disease and antimicrobial resistance. Previous studies have suggested that smooth bacteria can reversibly switch between the transparent and opaque forms, but the mechanism underlying morphotype transition has remained unknown. Using a clinical strain of M. avium ssp hominissuis, we show that transparent-to-opaque conversion can occur without reversible genetic rearrangement and is associated with deregulation and mutations in genes involved in peptidoglycan hydrolysis ( marP and ripA ), an interpretation supported by integrated phenotypic, genomic, and transcriptomic analyses. Macrophage infections demonstrate robust SmO morphotype–dependent activation of the NLRP3/ASC inflammasome. Analyses in a murine aerosol instillation model for pulmonary infection show that SmO, while unable to persist in the tissue, exhibits drastically increased capacity to colonize lungs compared to virulent SmT, a feature dependent on inflammasome activation. In contrast, SmT bacteria exhibit poor ability to colonize lungs but persist efficiently in an inflammasome-independent manner, likely explaining the selection for the SmT morphotype in patients. These results indicate a cell wall peptidoglycan remodeling–dependent mechanism for morphotype transition in M. avium and reveal discrete host–pathogen interactions and functional roles for SmT and SmO morphotypes during pulmonary infection.